BLOCKCHAIN AND THE VISUAL ARTS ECOSYSTEM: DISRUPTIVE IMPACTS ON DIGITAL ART OWNERSHIP, NFTS, AND CREATIVE ECONOMIES - Sane, Sandip; Tripathi, Diksha; Bhope, Anagha; Shah, Aditee Huparikar; Dongre, Rashmi; Raje, Harshal; Sudesh N. S (ShodhKosh: Journal of Visual and Performing Arts, 2025)
One of the ways in which blockchain technology is transforming the visual arts ecosystem is by providing decentralized, transparent, and verifiable systems of ownership, distribution, and value exchange of digital art. This paper analyzes how blockchain has been disruptive to visual arts in modern times, specifically in non-fungible tokens (NFTs), creative economies, and artist-collector relationships. Historically, the digital artworks were associated with the issues with provenance, copyright protection, scarcity, and justifiable monetization. Blockchain overcomes these weaknesses by providing immutable registries, smart contracts, and tokenization to allow artists to have verifiable ownership, determine authenticity, and earn automatic royalties on transactions in the secondary market. The study takes a conceptual and analytical structure by synthesising the extant literature, platform case studies and new blockchain-based art markets to assess the worth of NFTs in redefining artistic value, authorship and market forces. The results suggest that blockchain makes global art markets more democratic by decreasing the use of intermediaries including galleries and auction houses, which are central, and thus giving power to independent and new artists. Simultaneously, it cultivates new creative economies in which digital scramble, community contribution and speculative finance overlap. Nevertheless, the paper also singles out some fundamental challenges such as environmental sustainability issues, market unpredictability, regulatory ambiguity and the issues of artistic legitimacy and cultural value. The article presents the argument that although blockchain does not substitute the traditional art institutions, it supports them by providing hybrid ecosystems through integrations of physical and digital practices. All in all, the study suggests blockchain as a revolutionary infrastructure to the visual arts, reinventing ownership, trust, and economic frameworks and proposing a sustainable, ethical, and inclusive future to enable the long-term development of digital art ecosystems.